Validation and Comparison of Zwolle, TIMI, and GRACE Risk Scores for STEMI Patients Undergoing Primary Percutaneous Coronary Intervention in The Indonesian Population. - Asrial, An Aldia; Pudjiastuti, Anggit; Herry, Yan; Bahrudin, Udin (The Indonesian Heart Association, 2025)
In “Validation and Comparison of Zwolle, TIMI, and GRACE Risk Scores for STEMI Patients Undergoing Primary Percutaneous Coronary Intervention in The Indonesian Population” (Indonesian Journal of Cardiology, 43(2), 56-63. https://doi.org/10.30701/ijc.1324), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1324. The error occurs only in the PDF; the DOI listed in the article metadata is already correct.The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1324